A method of monitoring three-dimensional ground displacement in mining areas by integrating multiple InSAR methods. Issue 4 (16th February 2018) - Wang, Zhiwei; Yu, Shengwen; Tao, Qiuxiang; Liu, Guolin; Hao, Huadong; Wang, Ke; Zhou, Chuanyi
ABSTRACT: Underground mining often causes large-gradient vertical and horizontal displacement in ground surface, resulting in the losses of coherence and difficulties in phase unwrapping. This article presents an approach to determine three-dimensional ground displacements in mining areas with the large gradient or phase decorrelation by integrating multiple interferometric synthetic aperture radar (InSAR) methods. The core of the proposed method is that the offset-tracking method is employed to solve for the displacement with the large gradient or phase decorrelation. First, the displacements in the radar line-of-sight directions are obtained from two interferometric pairs with different viewing geometries by integrating the measurements of differential InSAR and offset tracking. Then, the displacements in the azimuthal directions are obtained from two interferometric pairs with different viewing geometries by integrating the measurements of multiple aperture interferometry and offset tracking. Finally, the three-dimensional ground displacement fields are inferred from these four independent, one-dimensional displacements using the least squares method and Helmert variance component estimation. We apply this method to obtain the three-dimensional ground displacement field in the Dongtan mine region. We compare the results with those of levelling and global positioning system surveys, and the root mean square errors of the results were 24 and 43 mm in the vertical direction and horizontal directions, respectively. The experimental results indicate that the proposed method can be used to estimate three-dimensional ground displacement fields in mining areas with large-gradient displacement and phase decorrelation.